Protease and sugarcane yeast in diets for broiler chicks - Moreira, Elvania Maria da Silva Costa; Dourado, Leilane Rocha Barros; Bastos, Hidaliana Paumerik Aguiar; Ribeiro, Mabell Nery; Silva, Sandra Regina Gomes da; Lopes, João Batista; Moreira Filho, Miguel Arcanjo; Lima, Stélio Bezerra Pinheiro de (Acta Scientiarum. Animal Sciences, 2020)
The objective of this study was to evaluate the inclusion of protease and sugarcane yeast in poultry diets on performance, organ weight, intestinal biometry, chemical composition and deposition of body nutrients in the 1 to 7-day old phase. The experimental design consisted of a randomized complete block design, in a factorial arrangement of 2 (without and with the enzyme protease) x3 (yeast levels: 0, 6 and 12%) +1 (positive control diet), totaling seven treatments with five replicates, birds per experimental unit. The treatments used consisted of a positive control diet and the others were the negative control, with reductions in nutritional levels of protein and amino acids by 4% requirement. In the negative control diets, protease enzyme was included in three levels of sugarcane yeast. In isolation, treatments with or without inclusion of protease influenced the chemical composition of the birds. The levels of yeast from sugarcane yeast presented effects for weight gain, feed conversion, moisture and crude protein in the nutrient deposition. The inclusion of protease in diets for broiler chicks cannot remedy the poor performance provided by the use of sugarcane yeast, in addition to presenting lower levels of deposition of body nutrients.